Transformational Leadership Style, Psychological Empowerment and Job Satisfaction in Greek Municipal Sport Organizations - Lefkothea Tsevairidou; Ourania Matsouka; Efstratia Tsitskari; Vassilios Gourgoulis; George Kosta (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
The aim of the present research was to examine the effects/correlations of transformational leadership style on employees' psychological empowerment in the context of Greek municipal sport organizations. Moreover, the second aim of the present study was to examine the correlation of employees' psychological empowerment on their job satisfaction in the same context of Greek municipal sport organizations. The sample of the research constituted of 30 managers and 247 employees of Greek municipal sport organizations, of Eastern Macedonia and Thrace, of Western Macedonia and of Central Macedonia. In an effort to investigate the specific concern, the managers completed the multifactor leadership questionnaire of Bass and Avolio (1997), while the employees completed the psychological empowerment instrument of Spreitzer (1995) and Minnesota Satisfaction Questionnaire (MSQ). SPSS 20 was used for the statistical data analysis. More specifically, regression analysis and Pearson's rank correlation was used for the variables that satisfied the affair of regularity, while for those variables that were not satisfied the affair of regularity was used non parametric Spearman's rank correlation coefficient. The results showed that self-determination, the dimension of psychological empowerment, had strong positive correlation with idealized influence attributes (IIA) (r=0.492; p=0.007), and strong negative correlation with idealized influence behavior (IIB) (r=-0.421; p=0.023) of transformational leadership style. Also, the study found significant positive correlation on psychological's empowerment dimensions with all job satisfaction's dimensions. Implications and directions for future research are discussed.